Resonance energy transfer study of hemoglobin binding to model lipid membranes - Kutsenko, O. K.; Gorbenko, G. P.; Trusova, V. M. (Biophysical Bulletin)
In the present study fluorescence resonance, energy transfer (FRET) technique was employed to obtain information about the structure of hemoglobin (Hb) complexes with model lipid membranes of different composition. For this purpose three membrane probes, 3-methoxybenzanthrone (MBA), 4- dimethylaminochalcone (DMC) and 6-propionyl-2-dimethylaminonaphthalene (Prodan) were assessed as possible donors for heme moiety of the protein. Model membranes were composed of zwitterionic lipid phosphatidylcholine (PC), anionic lipid cardiolipin (CL), and cholesterol (Chol). FRET measurements were interpreted in terms of the model of energy transfer in two-dimensional systems proposed by Fung and Stryer and further extended by Davenport et al. No FRET was observed between Prodan and Hb because Prodan under the employed experimental conditions was not distributed into the lipid bilayer. In the case of DMC, Hb-induced oxidative processes in the lipid phase hampered the estimation of Hb location in a lipid bilayer. Therefore, structural analysis of Hb-lipid complexes was carried out using MBA as a donor. First, the donor quantum yield, Förster radii, and fluorescence anisotropy of the probes have been measured. Second, the amount of Hb bound to model membranes was estimated in terms of the lattice models of large ligand adsorption to lipid bilayers allowing for the possibility of protein insertion into the membrane interior. Finally, the distance from the acceptor plane to the bilayer center and the depth of Hb penetration into the lipid bilayer were calculated. It was assumed that protein binds to membranes in the form of dimers and penetrates into the membrane interior. In neutral liposomes, Hb penetrates only to the depth of lipid headgroups. The observed higher extent of Hb penetration into Chol containing bilayer as compared to PC liposomes may be a consequence of specific Hb-Chol interaction. In the case of PC/CL liposomes, Hb was found to insert in the non-polar membrane region. Taking into account the possibility of forming the inverted hexagonal structures in the presence of CL, it cannot be excluded that Hb being entrapped in such structures, translocates through the membrane. If this phenomenon takes place, deeper Hb penetration into lipid bilayer might be expected. The obtained results can be useful for exact characterization of Hb binding to the membranes.